1994
DOI: 10.1128/iai.62.1.259-265.1994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipopolysaccharide (LPS) chain length on interactions of bactericidal/permeability-increasing protein and its bioactive 23-kilodalton NH2-terminal fragment with isolated LPS and intact Proteus mirabilis and Escherichia coli

Abstract: The target-specific cytotoxicity for gram-negative bacteria and the endotoxin-neutralizing activity of the 55-kDa bactericidal/Permeability-increasing protein (BPI) and its bioactive 23-kDa NH2-terminal fragment depend on the strong attraction of BPI for the lipid A region of lipopolysaccharides (LPS). We have shown before that smooth gram-negative bacteria with long-chain LPS are more resistant to BPI (especially holo-BPI) than are rough strains. It has been suggested that the high BPI resistance of some gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…These groups are shielded by the O‐antigen which includes many polar but uncharged glucosyl‐groups, rendering the negative charges less accessible. Indeed, BPI binding depends on the LPS O‐antigen chain length in Escherichia coli and Proteus mirabilis (Capodici et al ., 1994). It is important to note that modifications of the LPS also affect the efficiency of the TTSS (West et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These groups are shielded by the O‐antigen which includes many polar but uncharged glucosyl‐groups, rendering the negative charges less accessible. Indeed, BPI binding depends on the LPS O‐antigen chain length in Escherichia coli and Proteus mirabilis (Capodici et al ., 1994). It is important to note that modifications of the LPS also affect the efficiency of the TTSS (West et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…How LOS sialylation could influence rBPI 21 binding to the lipid A component of LPS is not known. Structure of polysaccharide can have an effect on the inhibitory effects of rBPI 21 on some LPSs (3). It has been demonstrated that mutants of E. coli that have incomplete LPS are much more sensitive to bactericidal permeability-increasing protein than are E. coli strains with intact LPS.…”
Section: Fig 7 Effect Of Rbpi 21 On Induction Of Cd62e Expression Onmentioning
confidence: 99%
“…It is interesting that although Gram-negative bacteria display variable sensitivity to BPI, the LPS-neutralizing activity of BPI is manifest with LPS also from bacteria strains resistant to antibacterial effects of BPI. Therefore, LPS neutralization and anti-inflammatory effects of BPI may be important functions of this protein [9,10].…”
Section: Introductionmentioning
confidence: 99%